2020
DOI: 10.1038/s41598-020-58269-z
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Behavioral Intervention for Tics reduces perception-action binding during inhibitory control in Gilles de la Tourette syndrome

Abstract: Gilles de la tourette Syndrome (GtS) is a developmental disorder. empirical studies and an emerging cognitive framework on GtS suggest that GtS is a disorder of abnormally strong 'perception-action binding'. Theoretical considerations imply that the effectiveness of long-established behavioral interventions might be related to a normalization of increased binding in GtS. this has not been tested yet. We examined the effect of a standardized Comprehensive Behavior Intervention for Tics (CBIT) in n = 21 adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 36 publications
1
27
0
1
Order By: Relevance
“…Findings related to the usefulness of TEC as an explanatory framework for GTS are also relevant for the understanding of the mechanisms of behavioral interventions. For instance, in a recent study, the effects of comprehensive behavioral intervention for tics on perception-action binding during inhibitory control were investigated (113). It was shown that the intervention altered inhibitory control in a condition where reconfigurations of perception-action bindings were necessary to perform inhibitory control.…”
Section: Tourette Syndrome In the Context Of The Theory Of Event Codingmentioning
confidence: 99%
“…Findings related to the usefulness of TEC as an explanatory framework for GTS are also relevant for the understanding of the mechanisms of behavioral interventions. For instance, in a recent study, the effects of comprehensive behavioral intervention for tics on perception-action binding during inhibitory control were investigated (113). It was shown that the intervention altered inhibitory control in a condition where reconfigurations of perception-action bindings were necessary to perform inhibitory control.…”
Section: Tourette Syndrome In the Context Of The Theory Of Event Codingmentioning
confidence: 99%
“…However, it is important to note that findings suggesting impairments in inhibitory control are not undisputed. There are also studies showing no difference (15,(81)(82)(83), sometimes depending on the difficulty to inhibit a response (12,84), or even enhanced performance (85)(86)(87) in inhibitory tasks in GTS. Also, the notion of a general impairment of inhibitory functions in GTS is contentious given the ability of these patients to actively suppress their tics, at least for certain periods of time (88).…”
Section: Long-range Frontal and Basal-ganglia-thalamo-cortical Circuimentioning
confidence: 99%
“…Feature binding has been found to be altered in aging (Hommel et al 2011) and neurological conditions such as Tourette syndrome (Kleimaker et al 2020a, b;Petruo et al 2019Petruo et al , 2020, Parkinson's disease (Colzato et al 2012) and stress (Frings et al 2013). Against this background, in order to ameliorate these conditions, there is a rising interest for enhancing practices aimed on optimizing feature binding.…”
mentioning
confidence: 99%